Out of the past - Duff, Warren B. 1904-1973; Tourneur, Jacques 1904-1977; Mitchum, Robert 1917-1997; Greer, Jane; Douglas, Kirk 1916-2020 (Turner Home Entertainment, 2004)
Former private detective Jeff Bailey is trying to lead a quiet life, but his past comes back to haunt him and he finds himself framed for murder